Hydro-salinity balance to monitor soil salinity at field scale due to brackish irrigation water - Libutti A.; Florio M.; Monteleone M.; Disciglio G.; Tarantino E. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
The aim of the trial was to detect the risk of soil salinity due to brackish irrigation. A permanent experimental field-unit was established in autumn 2006; three plots were delimited; at the center of each plot an artificial draining basin was arranged digging the soil out of a trench; the bottom of each trench was covered with a plastic sheet in order to prevent water percolation; a set of drains were displaced over the plastic cover to collect the percolating water and conveying it into tanks placed at the edge of each plot. The trenches were then filled with the same soil obtained by the excavating procedure. The electrical conductivity of the irrigation water (ECi) increased from 4.7 to 5.3 dS m-1 along the crop cycle. Soil ECe (electrical conductivity of soil saturated water extract) was periodically measured by soil samplings. Seasonal farmer irrigation was 544 mm while rain amounts were equal to 117 mm. Along the crop cycle, an increasing soil salinization occurred, starting from 2.4 dS m-1 up to 6.6 dS m-1. Due to leaching, at harvest, the soil ECe decreased to 4.8 dS m-1. Approximately, a 25 percent of yield reduction was recorded as compared to contiguous field irrigated with good water quality. A leaching fraction of approximately 10 percent resulted from the water balance while almost 20 percent of salt was removed from the soil profile with respect to the salt load bring about with irrigation. That means an actual leaching efficiency of approximately 220 kg ha-1 per each percent point of leached water.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)